PENGEMBANGAN SISTEM INFORMASI MONITORING PRAKTIK KERJA LAPANGAN BBPOM MATARAM DENGAN METODE RAPID APPLICATION DEVELOPMENT - Bagas Adinata; Nadiyasari Agitha; Ida Bagus Ketut Widiartha (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2026)
The Mataram National Agency of Drug and Food Control (BBPOM Mataram) requires an information system to manage internship participants’ data more effectively. The administrative process has been carried out manually, which often leads to inefficiency and potential errors in data storage. This study aims to develop a web-based information system that integrates the entire internship process, including application submission, entrance selection through pre-test, attendance recording, daily activity documentation, and final score calculation based on attendance and activities. The system was developed using the Rapid Application Development (RAD) method, which emphasizes iterative prototyping and user feedback to accelerate the development process. System testing was conducted using the black-box testing method to evaluate the functionality of each feature according to the requirements. In addition, usability testing was performed using the System Usability Scale (SUS), resulting in a score of 79,16, which indicates that the system is considered Good in terms of usability. The test results show that all system features function properly and meet the specified requirements. The implementation of this system supports BBPOM Mataram in improving efficiency, accuracy, and integration in managing internship participant data.